Effectiveness of Probiotics in Semi-Intensive Pond Cultivation: A Study on the Growth of White Shrimp (Litopenaeus vannamei) Using Bacillus spp. and Lactobacillus spp. - Harminto Harminto; Ayu Rizki Amelia; Monica Ryan; Siti Aisyah (Grouper)
Whiteleg shrimp (Litopenaeus vannamei) cultivation is one of the rapidly growing aquaculture sectors in Indonesia, especially in West Sumatra Province. However, the success of this cultivation is greatly influenced by feed efficiency, water quality, and shrimp health. The use of probiotics is one of the strategies that are widely developed to improve cultivation performance in a sustainable and environmentally friendly manner. This study aims to compare the effectiveness of two types of probiotics, namely Bacillus spp. and Lactobacillus spp., on the growth and survival of whiteleg shrimp in a semi-intensive pond system. The study was conducted experimentally in Padang Pariaman Regency using a Completely Randomized Design (CRD) consisting of three treatments and three replications: P1 (control without probiotics), P2 (Bacillus spp. probiotics), and P3 (Lactobacillus spp. probiotics). The parameters observed included daily growth rate, survival rate, feed conversion efficiency (FCR), and water quality (pH, DO, NH₃, and salinity). Data were analyzed using ANOVA test and continued with DMRT test at a significance level of 5%. The results showed that the P2 treatment gave the best results significantly on all main parameters. Bacillus spp. has been shown to increase growth rate, survival rate, feed efficiency, and stabilize pond water quality. The P3 treatment showed intermediate results, while P1 showed the lowest performance. Thus, Bacillus spp. is the most effective probiotic to support vaname shrimp cultivation in a semi-intensive system.